2012
DOI: 10.1590/s1806-37132012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de um protocolo de desmame de ventilação mecânica na taxa de falha de extubação em pacientes de difícil desmame

Abstract: Objective: To determine whether the predictive accuracy of clinical judgment alone can be improved by supplementing it with an objective weaning protocol as a decision support tool. Methods: This was a multicenter prospective cohort study carried out at three medical/surgical ICUs. The study involved all consecutive difficultto-wean ICU patients (failure in the first spontaneous breathing trial [SBT]), on mechanical ventilation (MV) for more than 48 h, admitted between January of 2002 and December of 2005. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
20

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
1
6
0
20
Order By: Relevance
“…( 21 , 22 ) We found no association between the reason for reintubation and in-hospital mortality, a finding that corroborates those of Menon et al ( 23 ) In contrast with our results, the results of a study conducted by Epstein et al ( 24 ) showed a higher mortality in patients who were reintubated because of nonairway problems. It is plausible that, in patients who are reintubated because of upper airway obstruction, acute respiratory failure can be immediately corrected, whereas organ dysfunction cannot.…”
Section: Discussionsupporting
confidence: 88%
“…( 21 , 22 ) We found no association between the reason for reintubation and in-hospital mortality, a finding that corroborates those of Menon et al ( 23 ) In contrast with our results, the results of a study conducted by Epstein et al ( 24 ) showed a higher mortality in patients who were reintubated because of nonairway problems. It is plausible that, in patients who are reintubated because of upper airway obstruction, acute respiratory failure can be immediately corrected, whereas organ dysfunction cannot.…”
Section: Discussionsupporting
confidence: 88%
“…A retirada precoce da VM também auxilia na melhora do estado do paciente reduzindo a ocorrência de complicações como a Pneumonia Associada à Ventilação Mecânica (PAV) e realização de traqueostomia, fatores estes, que aumentam a morbidade e os custos relacionados a UTI. (1,2,6,7) O processo de interrupção do suporte ventilatório mecânico é iniciado quando o paciente melhora da causa que o levou a necessidade da ventilação. (4,6)…”
Section: Introductionunclassified
“…(1,2,6,7) O processo de interrupção do suporte ventilatório mecânico é iniciado quando o paciente melhora da causa que o levou a necessidade da ventilação. (4,6)…”
Section: Introductionunclassified
See 1 more Smart Citation
“…( 35 , 36 ) The use of ventilatory support and extracorporeal membrane oxygenation was the subject of a study conducted in the city of São Paulo ( 37 ) and of an editorial authored by Professor Alan Morris of Salt Lake City, Utah. ( 38 ) There were three publications on weaning from mechanical ventilation: an original article on weaning protocols conducted in the Brazilian state of Rio Grande do Sul, ( 39 ) ; a review article on predictive parameters ( 40 ) ; and an editorial by Professor Martin Tobin of Chicago, Illinois. ( 41 ) Other emerging areas, such as pulmonary circulation, smoking, environmental exposure, bronchoscopy, and sleep-disordered breathing, were also addressed.…”
mentioning
confidence: 99%